Development of Sharia-Based Financial Products and Microfinance in Islamic Economy - Ratnawita, Ratnawita; Nurdiani, Tanti Widia; Judijanto, Loso; Fali, Ibrahim Mallam (West Science Journal Economic and Entrepreneurship, 2023)
Within the context of Islamic economics, this study examines the dynamic interactions between the growth of microfinance and the creation of financial products based on Sharia. The study used a quantitative research methodology to examine significant variables, including the expansion of financial instruments that comply with Sharia law, the availability of microfinance, and the socioeconomic consequences of these endeavors. The study covers a wide range of Islamic economies and uses statistical methods to evaluate the relationship between the uptake of financial products based on Sharia and the improvement of microfinance services. The results provide quantitative insights into how Islamic finance and microfinance are developing, with implications for future research projects, financial institutions, and regulators.